Exploring the contribution of self-help groups to sexual and reproductive health and HIV outcomes for female sex workers in sub-Saharan Africa: A scoping review. - Gracious Madimutsa; Fortunate Machingura; Owen Nyamwanza; Frances M Cowan; Webster Mavhu (PLOS Global Public Health)
Self-help groups (SHGs) have been effective in improving the health and wellbeing of women generally but there is little evidence on whether and how they improve HIV and sexual and reproductive health (SRH) outcomes among female sex workers (FSWs), particularly in sub-Saharan Africa. This scoping review attempted to address this gap by identifying and analysing literature on SHGs for FSWs in sub-Saharan Africa. The review followed the 5-step framework developed by Arksey and O'Malley: 1) defining the research question, 2) identifying relevant studies, 3) selecting studies, 4) charting the data, and 5) collating, summarising, and reporting the results. We searched three databases (CINAHL, Medline and Global Health) for peer-reviewed articles published between 1 January 2000 and 30 September 2024. We identified eleven studies: two were quantitative, seven were qualitative and two were mixed methods. Studies were from seven countries in sub-Saharan Africa. The studies suggested that SHGs can improve SRH outcomes and reduce HIV vulnerabilities among FSWs by providing emotional and financial support, health education, linkage to care and social capital (i.e., benefits derived from association). The studies also highlighted the need for tailored interventions that address the unique needs and challenges faced by FSWs. This scoping review highlights the crucial contribution that SHGs make in promoting social cohesion, SRH and HIV outcomes among FSWs across seven countries in sub-Saharan Africa. To build resilience and facilitate better health outcomes, FSWs need to be empowered at individual, societal and resource levels through SHGs. Further research on the formation, structure, leadership, sustainability of SHGs and contextual factors, is required for understanding the best practices of their implementation to achieve long-term success.